Collective action in poverty reduction programs - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Over half of the hungry people in the world are small-scale farmers, herders, and fishers, who produce food but cannot reliably feed themselves and their families. Nevertheless, poor people are themselves working to improve their lives. Even when their individual resources may be weak, Collective Action in Poverty Reduction Programs working together can help overcome limitations of wealth, farm size, and bargaining power. Collective action can provide an instrument for addressing poverty through natural resource management, income generation, reducing vulnerability, providing critical services, and allocation of rights. Collective action offers the potential to build assets and overcome poverty traps.